Prediction of stillbirth: an umbrella review of evaluation of prognostic variables. (13th October 2020) - Townsend, R; Sileo, FG; Allotey, J; Dodds, J; Heazell, A; Jorgensen, L; Kim, VB; Magee, L; Mol, B; Sandall, J; Smith, GCS; Thilaganathan, B; et al.
Abstract: Background: Stillbirth accounts for over 2 million deaths a year worldwide and rates remains stubbornly high. Multivariable prediction models may be key to individualised monitoring, intervention or early birth in pregnancy to prevent stillbirth. Objectives: To collate and evaluate systematic reviews of factors associated with stillbirth in order to identify variables relevant to prediction model development. Search strategy: MEDLINE, Embase, DARE and Cochrane Library databases and reference lists were searched up to November 2019. Selection criteria: We included systematic reviews of association of individual variables with stillbirth without language restriction. Data collection and analysis: Abstract screening and data extraction were conducted in duplicate. Methodological quality was assessed using AMSTAR and QUIPS criteria. The evidence supporting association with each variable was graded. Results: The search identified 1198 citations. Sixty‐nine systematic reviews reporting 64 variables were included. The most frequently reported were maternal age ( n  = 5), body mass index ( n  = 6) and maternal diabetes ( n  = 5). Uterine artery Doppler appeared to have the best performance of any single test for stillbirth. The strongest evidence of association was for nulliparity and pre‐existing hypertension. Conclusion: We have identified variables relevant to the development of prediction models for stillbirth. Age, parity and prior adverse pregnancy outcomes had a more convincing association than the best performing tests, which were PAPP‐A, PlGF and UtAD. The evidence was limited by high heterogeneity and lack of data on intervention bias. Tweetable abstract: Review shows key predictors for use in developing models predicting stillbirth include age, prior pregnancy outcome and PAPP‐A, PLGF and Uterine artery Doppler. Tweetable abstract: Review shows key predictors for use in developing models predicting stillbirth include age, prior pregnancy outcome and PAPP‐A, PLGF and Uterine artery Doppler.